Papers of Eric Gross - Gross, Eric, 1926-2011. (1931)
MS Acc12.073 comprises personal papers and music manuscripts (48 boxes, 61 folio items).
Manuscript reference number.: MS Acc12.073.
Also available online
Eric Gross AM was an Austrian-Australian academic, pianist, composer, arranger and conductor. Further biographical information available at
Keywords: Gross, Eric, -- 1926-2011 -- Archives; Pianists -- Australia -- Archives; Composers -- Australia -- Archives; Conductors (Music) -- Australia -- Archives; Music teachers -- Australia -- Archives; Piano music; Pianists; Composers; Conductors (Music).; Academics